Changes in Health Insurance Enrollment Since 2013 Evidence from the RAND Health Reform Opinion Study - Carman, Katherine Grace (RAND Corporation, 2014)
This paper examines changes in enrollment in health care coverage in the wake of the implementation of the Affordable Care Act using results from the RAND's Health Reform Opinion Study.